EDUCATIONAL TRANSFORMATION IN INDONESIA: BETWEEN CHALLENGES AND OPPORTUNITIES IN THE FUTURE - Sabrina Azzikra Emilia; Maisa Wahyuni Lubis; Nadiyatul Husna Lubis; Nabila Zahira Matondang; Umam Rasyid Tifada; Ayu Astuti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Education in Indonesia faces major challenges, including disparities in access and quality between urban and rural areas. This article discusses these challenges and opportunities for transformation through the use of technology, strengthening character education, and developing 21st-century skills. By adapting technology- and skills-based curricula, and strengthening collaboration between the government, private sector, and communities, Indonesian education can be more inclusive and relevant to future needs.